Methodological Features of Determining the External Specific Surface Area of High-Strength Synthetic Diamond Grinding Powders - Petasyuk, Grigorii A. (Journal of Coating Science and Technology, 2026)
A new indirect-analytical method for determining the external specific surface area of high-strength synthetic diamond grinding powders has been created. The method is based on the well-known from publications fractional-averaging approach to the indirect analytical determining of technological properties of high-strength synthetic diamond grinding powders. The main idea of the proposed new method is to take into account the features of the real 3D morphology of grains of such grinding powders. The possibility and expediency of using in similar problems in one sense of calculation, both a methodological scheme with an extrapolation-affine 3D grain model and a methodological scheme with actual 3D grain shape, have been substantiated. The proposed methodological scheme allows for the real morphology of grains of such grinding powders to be considered, which provides greater reliability of the indices of their technological properties obtained. The practical application of the proposed new method for determining the external specific surface area of the standard Ukrainian State Standard DSTU 3292–95 high-strength synthetic diamond grinding powder AC400 500/400 is illustrated. The new method we proposed was used as the basis for comparison. The value of the external specific surface area of the specified grinding powder calculated by this method was 4.3213 m2/kg. Applying the commonly used method for this purpose gave the result of 4.1324 m2/kg. The comparative analysis showed that the commonly used known method gives 1.046 times (4.37%) lower values of the external specific surface area for the specified grinding powder than the proposed new method. This indicates the advantage of the proposed new method for determining the external specific surface area of high-strength synthetic diamond grinding powders.